1994
DOI: 10.3892/or_00000236
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus detection in invasive and pre-invasive lesions of the uterine cervix

Abstract: Abstract. In the present study, our aim was to investigate whether EBV DNA could be found in association with invasive and pre-invasive cervical cancer lesions. We hypothesize that EBV is not merely a commensal agent when present in malignant cervical lesions. DNA was extracted from cervical scrapings followed by nested PCR-based amplification. The patients were 66 women with high grade cervical intraepithelial neoplasia and 14 women with invasive cervical cancer. The control group consisted of 89 women with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Genital coinfection of these viruses may disrupt the mucosal epithelial barrier (Hebner and Laimins, 2006) and the different viruses may influence each other in many ways, such as viral entry and clearance (Blanco et al, 2020). Consistent with previous reports (Santos et al, 2009;Kienka et al, 2019;Cameron et al, 2020;Joharinia et al, 2020), we revealed a significant association between EBV and HPV coinfection and CIN2+, suggesting that coinfection of EBV and HPV is a potential risk factor in carcinogenesis. While there is a close relationship between EBV infection and HPV-related cervical cancers, the underlying mechanisms remain unclear.…”
Section: Discussionsupporting
confidence: 91%
“…Genital coinfection of these viruses may disrupt the mucosal epithelial barrier (Hebner and Laimins, 2006) and the different viruses may influence each other in many ways, such as viral entry and clearance (Blanco et al, 2020). Consistent with previous reports (Santos et al, 2009;Kienka et al, 2019;Cameron et al, 2020;Joharinia et al, 2020), we revealed a significant association between EBV and HPV coinfection and CIN2+, suggesting that coinfection of EBV and HPV is a potential risk factor in carcinogenesis. While there is a close relationship between EBV infection and HPV-related cervical cancers, the underlying mechanisms remain unclear.…”
Section: Discussionsupporting
confidence: 91%
“…In one study from Thailand, the EBV genome was found in 13.4% of normal cervical samples, 29.4% of low-grade squamous intraepithelial lesions (LSILs), 49.4% of high-grade squamous intraepithelial lesions (HSIL), and 35% of cervical cancer samples [ 23 ]. In a study from Brazil, the EBV genome was detected in 8.99%, 21.2%, and 64.3% of normal, premalignant, and malignant cervical samples, respectively [ 29 ]. In a study from Portugal, the EBV genome was found in 16.7% of normal samples, 9.5% of cervical intraepithelial neoplasia (CIN 1), 4.5% of CIN 2/3, and 22.2% of cervical cancer [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between EBV LMP1 and HPV viral proteins altered NF-κB and MAPK signaling, among others, in a murine model [207], while another study highlighted the necessity of HPV viral oncoproteins E6 and E7 in EBV lytic replication in oral keratinocytes [208]. A helper role of EBV in cervical cancer development has been suggested by several studies due to the presence of both HPV and EBV DNA sequences in malignant tissues [209][210][211][212][213][214][215][216].…”
Section: Other Co-infectionsmentioning
confidence: 99%